66.0k views
6 votes
Solve the system using elimination.
3x + 5y = -2
-x + 2y = 8
([?], [ ]

Solve the system using elimination. 3x + 5y = -2 -x + 2y = 8 ([?], [ ]-example-1
User Nidia
by
5.0k points

1 Answer

5 votes

Answer:

Explanation:

To eliminate the x terms, first multiply the second equation by 3:

-3x + 6y = 24

then add it to the first equation:

3x + 5y = -2

-3x + 6y = 24

------------------

0x + 11y = 22

y = 2

plug the value of y into one of the equations:

-x + 2(2) = 8

x = 4-8 = -4

(x,y) = (-4, 2)

User TheDrot
by
5.1k points